Improving the multicultural curriculum of Iranian educational system based on Michel Foucault and Henry Giroux s views - Mahdi Sobhāni Nejād; Najmeh Ahmadābādi Ārāni; Ali Abdolāhyār (فصلنامه نوآوری‌های آموزشی, 2017)
This paper was an attempt to improve the multicultural curriculum of Iranian educational system based on Michel Foucault and Henry Girouxs views, using conceptual analysis and deductive approach to research. Findings showed that multicultural curriculum is based on the concepts such as social justice, equality training and facilitating the educational experiences. Among the great thinkers of multicultural education, Michel Foucault and Henry Giroux have presented significant issues in the multicultural curriculum. Foucault considers education as more personal, specific and local, so that in the field of education, the tone of the curriculum and teacher should be polyphonic. Besides, Giroux considers education as being multicultural, supporting racial and ethnic minorities. Giroux believes that the curriculum should be the domain of emerging different sounds of culture, race and gender and no group should be marginalized. With regard to the educational ideas of Foucault and Giroux in the field of multicultural curriculum, we can use the assistant and complementary approaches such as, border education, critical education in education system, innovation in educational content, enhancing the critical thinking of students, qualitative research methods in teaching-learning process, and developing various school activities in order to improve the multicultural curriculum in Iranian educational system.